A physics-informed approach for post-event regional diagnosis of arch dam cracking - Ruiqi Wu; Xiaohu Du; Ziwei Li; Huijun Qi; Tongchun Li; Chaoning Lin (Engineering Structures, 2026)

Antibacterial gold nanoclusters: Protamine-coated, enzyme-inhibiting nanoparticles combat drug-resistant bacteria and accelerate wound healing - Chengcheng Lin; Ziwei Chen; Ping Zhang; Peng Chen; Yanyan Cui; Xueling Chang; Jian Yang (Journal of Environmental Sciences, 2026)

Cobalt nanoparticles-embedded wood-derived biochar as a peroxymonosulfate activator for wastewater purification - Piao Xu; Yangzhuo He; Wenyang Li; Lin Hu; Ziwei Wang; Hong Qin; Fuqi Wu; Ying Zeng; Shengyi Wu; Yuan Zhu (Chemical Engineering Journal, 2026)

BcSak1-mediated adaption to low temperature in Botrytis cinerea represents optional targets for management of cold-tolerant diseases on harvested fruits - Ziwei Su; Yuxuan Lin; Xinyi Long; Jiaxi Zhang; Yin Li; Chuanxi Zhu; Wenjin Yan; Congcong Wang; Yiwen Wang; Junwei Zhao; Xiang Li; Aruppillai Suthaparan; et al. (Postharvest Biology and Technology, 2026)

Enhanced photodynamic inactivation against Listeria monocytogenes under blue light mediated by carbon dots derived from ‘Shatian’ pomelo peels for ready-to-eat sausage preservation - Ce Shi; Rui Yang; Xinyu Huang; Ziwei Liang; Layla A. Alahmari; Maha Abdullah Alwaili; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2026)

Enhanced elimination efficiency of rhamnolipid functionalized-nanoliposomes loaded with diacetyl against Listeria monocytogenes biofilms on food-contact surfaces and vegetables - Ce Shi; Yangyang Chen; Xinyu Huang; Ziwei Liang; Tariq Aziz; Shereen Magdy Korany; Fahad Al-Asmari; Amal A. Mohamed; Haiying Cui; Lin Lin (Food Control, 2026)

Nationwide occurrence of p-phenylenediamine antioxidants and their derivatives in coastal sediments across China - Zilan Wu; Xing Liu; Tian Lin; Yawen Wei; Jintao Xu; Jianzhong Li; Xi Liu; Ziwei Yao (Marine Pollution Bulletin, 2026)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

Dust transport and impacts on secondary aerosol formation: Contrasting strong dust and floating dust events - Yanfen Lin; Qingyan Fu; Ziwei Liu; Zhijian Ding; Fan Yang; Ali Darvishi Boloorani; Cheng Huang; Juntao Huo; Qian Wang; Jia Chen; Qiongzhen Wang; Sabur F. Abdullaev; et al. (Atmospheric Environment, 2026)

Leucobacter faecis sp. nov., a Novel Actinomycete Isolated from Bat Feces of Rousettus and Hipposideros spp. - Yuyuan Huang; Jing Yang; Qinglian Qin; Zedan Yang; Xiaoting Wei; Ziwei Lin; Wenbo Luo; Wudi Wei; Zongxiang Yuan; Li Ye; Junjun Jiang; Shan Lu; et al. (Current Microbiology, 2026)

Analysis on transfer pricing of sea area use rights based on market equilibrium theory - Junjie Lin; Lihai Zheng; Ziwei Zhou; Zhelin Chen; Qun Zhang; Yuanzhu Wei (Frontiers in Marine Science, 2026)
The marketization of sea area use rights is a critical mechanism for optimizing marine resource allocation efficiency and achieving the high-quality development of marine economy. Combining the natural attributes of marine resources with policy constraints, this study establishes a supply–demand theoretical model for sea area use rights transfer within the market equilibrium theory framework. Through model solving and equilibrium analysis, it elucidates the core factors influencing stakeholders’ willingness, and investigates the mechanism through which market forces affect the equilibrium transaction volume, price, and economic efficiency. The numerical simulation results evidence the effectiveness and feasibility of the theoretical model. The study finds that: (1) The market forces significantly shapes the sea area transfer equilibrium. Compared with competitive market, a monopoly will lead to a decrease in the equilibrium trading volume and price, and lower economic efficiency. (2) Consistency of the impact of exogenous factors on the market equilibrium. Given other factors, exogenous factors affect stakeholders’ willingness on equilibrium trading volume and price uniformly in competitive and monopolistic markets. This study develops an integrated equilibrium framework for sea area use rights transfer, incorporating micro-entity heterogeneity into the theoretical structure. It bridges general equilibrium theory with the specific institutional domain of sea area use rights transfer, extends the application boundary of equilibrium economics within marine resource management, and provides a new perspective for marine resource allocation research.

Uncertainty-aware life cycle assessment of alternative urban water supply strategies with a case study of Hong Kong - Yu-yao Wang; Chok Hang Yeung; Pei Wang; Ziwei He; Weiwei Zhang; Chencheng Dong; Lin Lin; Xiao-yan Li (Sustainable Cities and Society, 2026)

Microbially driven microplastic degradation: From mining functional microbiota to enhancing remediation potential in diverse environments - Xin Hou; Ruijia Jing; Yunan Lin; Ziwei Chen; Changjun Li; Zhiyun Wang; Xianhua Liu (Journal of Hazardous Materials, 2026)

Hierarchical Studies in TRAP2 Mice Demonstrate that Neuronal Activation and Mitochondrial Networks Integration Constitute the Key Mechanism Underlying Painful Syncope - Xueyin Pu; Yulu Xia; Ziwei Ni; Changlei Zhu; Kunlong Zhang; Bozhi Liu; Rui Lin; Jingxuan Zhu; Hui Liu; Shujiao Li; Yunqiang Huang; Feifei Wu; et al. (Neuroscience Bulletin, 2026)

PigTracker: Sequential-vertices-based tracking framework for intelligent pig farming - Weijia Lin; Xinyuan He; Ziwei Li; Zhixiong Zeng; Yanhua Liu; Enli Lyu; Junduan Huang (Computers and Electronics in Agriculture, 2026)

Compound marine-terrestrial heat extremes exacerbate economic growth inequality in global coastal zones - Wenyue Cao; Ming Luo; Lijie Lin; Ziwei Huang; Sijia Wu; Tao Pei (Science Bulletin, 2026)

Co-occurrence and risk assessment of ultraviolet filters and fragrances in marine bathing beaches of Dalian, Northern China - Mimi Zhang; Helin Sun; Gu Tao; Yupu Li; Xing Liu; Zilan Wu; Tian Lin; Ziwei Yao (Regional Studies in Marine Science, 2026)

Occurrence and distribution of waterborne substituted p-phenylenediamine antioxidants and their derivatives in coastal areas of China - Zilan Wu; Xing Liu; Tian Lin; Jianzhong Li; Xi Liu; Ziwei Yao (Marine Environmental Research, 2026)

Beyond saponins: An integrated mass spectrometry strategy for profiling, spatial mapping, and rapid authentication of non-saponin constituents in Panax species - Wenxiang Fan; Ziwei Li; Longchan Liu; Linnan Li; Rufeng Wang; Zhengtao Wang; Qiong Lai; Lin Zheng; Li Yang (Food Research International, 2026)

Advanced wick design in solar multistage distillation for on-site water recycling and salt recovery during saline soil remediation - Canjie Lin; Chao Wang; Yang Liu; Changting Wang; Ziwei Liao; Yuyou Lin; Tingting Zheng; Jinjuan Chen; Bolun Peng; Jianping Cao; Bei Liu; Lingyue Zhang; et al. (Chemical Engineering Journal, 2026)

PigInstance: An efficient Pig Instance segmentation framework for intelligent pig farming - Weijia Lin; Xinyuan He; Ziwei Li; Enli Lyu; Yanhua Liu; Zhixiong Zeng; Junduan Huang (Computers and Electronics in Agriculture, 2026)

Molecular engineering of benzoselenazole-based covalent organic frameworks for boosting photocatalytic hydrogen peroxide production in water and air - Ziwei Du; Chenxiang Lin; Yuchen Jin; Jia Chen; Tengyue Wang; Zhixuan Wang; Xu Ding; Chao Liu (Chemical Engineering Journal, 2026)

Optimization of pediatric dosing regimens for aztreonam and amoxicillin/clavulanate combination therapy against multidrug-resistant bacteria - Lili Wang; Mengyuan Wu; Lin Qu; Pengfei Wang; Ziwei Yu; Hua Deng; Frederico S. Martins; Jiayuan Zhang; Da Rong; Mingming Yu; Zhihua Lv; Sherwin K. B. Sy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Untargeted metabolomics analysis of foxtail millet fermented with Pleurotus geesteranus: Insights into the nutritional and antioxidant profiles - Tong Lin; Ziwei Zhang; Ruolin Shi; Gongjian Fan; Chunyan Xie (Food Chemistry, 2026)

Time-variant deformation prediction and reliability assessment of slopes based on dynamic Bayesian model averaging - Chenbo Zhao; Chaoning Lin; Fei Wang; Huijun Qi; Ziwei Li; Tongchun Li; Yukun He (Engineering Geology, 2026)

Side-deep placement of controlled-release urea combined with alternate wetting and drying irrigation achieves sustainable intensification of rice production in the rice–wheat system - Yuan Wang; Li Zhang; Kai Ming; Lin Cao; Song Guo; Jiaming Lu; Ziwei Li; Weiling Wang; Can Zhao; Fengping Yang; Ke Xu; Hongcheng Zhang; et al. (Field Crops Research, 2026)

Regime Shift from Macrophytes to Algal Dominance Enhances Lake Carbon Persistence: Molecular Evidence from DOM Transformation - Ziwei Zhang; Huanjun Zhang; Yi Li; Wangkai Fang; Li Lin (Journal of Environmental Sciences, 2026)

Mechanism and dynamic evolution of LED irradiation on volatile metabolites: A novel strategy for optimizing aroma quality in innovative black tea - Jihang He; Xinru Yu; Yunzhi Hao; Qiuming Li; Qingyang Wu; Xiaoxi Ou; Ying Xu; Hongzheng Lin; Ziwei Zhou; Yun Sun (Food Chemistry, 2026)

Magic chain-flip triboelectric nanogenerator for multi-mode wind and raindrop energy harvesting - Mingxia Chen; Jiahong Yang; Rui Gu; Hai Yan; Zhenghao Li; Siqi Sun; Nuo Xu; Ziwei Huo; Zhong Lin Wang; Qijun Sun; Xiangde Lin (Chemical Engineering Journal, 2026)

Effect of quorum sensing signal molecular analog 4-hydroxy-5-methyl-3(2H)-furanone on the microbial diversity and flavor characteristics of Sichuan Paocai - Chunhui Deng; Qin Peng; Xia Lin; Yue Shu; Shengshuai Li; Yunlong Song; Hong Kong; Lei Liu; Ziwei Liang; Yu Rao (International Journal of Food Microbiology, 2026)

Ecological presence and functional role of bacteriophages in fermented vegetables - Xia Lin; Chunhui Deng; Yue Shu; Shengshuai Li; Yunlong Song; Hong Kong; Ziwei Liang; Lei Liu; Yu Rao (Food Microbiology, 2026)

BreathFIT: Liquid metal-PDMS sticky conductors and AuNPs/MXene biosensors for synchronous EMG-lactate monitoring in respiratory health - Yang Liu; Zixin Lin; Yuetao Zhang; Xinyu Zhang; Zhiqi Li; Rubing Xiong; Chunxiao Long; Jiaqi Huang; Can Liu; Ziwei Zheng; Dan Li; Yongchang Ouyang; et al. (Chemical Engineering Journal, 2025)

Triple-pronged strategy: A theranostic hydrogel platform with near-infrared chemiluminescence imaging-guided sonodynamic therapy for bacterial-infected wound healing - Jiaxin Yang; Kaijia Lin; Ke Xu; Liping Zhang; Qian Zhang; Gelin Xu; Yachao Wang; Haixing Feng; Yayun Xu; Yanqin Fan; Ziwei Wang; Zihan Wu; et al. (Chemical Engineering Journal, 2025)

The mechanism of p38 MAPK, NF-κB, and IL-6 in T-2 toxin and/or selenium deficiency induced spleen injury - Xiang Xiao; Rongqi Xiang; Jiaxin Liu; Ziwei Guo; Haobiao Liu; Xue lin; Miaoye Bao; Viscardi Angelo; Jing Han (Immunologic Research, 2025)

PANoptosis-related genes in the prognosis and immune landscape of hepatocellular carcinoma - Xiaowu Wang; Liangchen Qu; Zhikai Wen; Zhixuan Wu; Yuxiang Xue; Xuejia Yang; Ziwei Yuan; Yangyang Guo; Xingcheng Lin (Immunologic Research, 2025)

Unraveling profiles of organic ultraviolet filters in coastal waters of the East China Marginal Seas - Zilan Wu; Xuan Jia; Xing Liu; Xiaodan Pei; Tian Lin; Jianzhong Li; Xi Liu; Yuan Gao; Ziwei Yao (Environmental Pollution, 2025)

Spatial distribution, potential sources, and dry deposition fluxes of per- and polyfluoroalkyl substances (PFAS) in atmospheric particles (PM2.5) in the offshore eastern China sea (OECS) - Hao Sun; Shuai Sun; Xuan Jia; Yadi Lou; Xing Liu; Zilan Wu; Yitao Pan; Zhongsheng Lin; Ziwei Yao; Jianmin Chen (Atmospheric Environment, 2025)

Dam operation changed the transport patterns of microplastics - from a global perspective - Yuling Chen; Li Lin; Yi Li; Yu Gao; Lei Dong; Xiong Pan; Ziwei Guo (Environmental Pollution, 2025)

Interface iodine management strategy towards high-efficiency and stable perovskite solar cells - Jiaqi Zhang; Yanzhuo Gou; Weideren Dai; Bowen Zhou; Jinyi Zeng; Zimeng Zhu; Ziwei Zhang; Tao Mei; Liangyou Lin; Xianbao Wang; Qidong Tai; Jinhua Li (Chemical Engineering Journal, 2025)

The threat of diaphragm closure to thermal runaway during battery charging - Jianqi Zhang; Tao Fan; Zhengnan Liu; Lin Yu; Yuhui Wang; FangZhou Li; Shuai Yuan; Chongye Chang; Kuo Wang; Ziwei Song; Xinming Qian; Qing Wang (Chemical Engineering Journal, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

Photocatalytic degradation of jellyfish polyps: A sustainable approach to combat jellyfish blooms - Wei Zhang; Jinzeng Gu; Jianing Lin; Song Feng; Ziwei Wang; Zhenhui Gao (Marine Pollution Bulletin, 2025)

Constraining anthropogenic CO2 emissions using dense observations from OCO-3: Disentangling observed imprints over Xiamen-Zhangzhou-Quanzhou metropolitan area and challenges - Xinxin Ye; Weijiao Li; Thomas Lauvaux; Shuifa Lin; Ziwei Zhang; Yunxiao Lin; Jingfen Hua; Qin You; Jianyi Lin (Urban Climate, 2025)

Converting building waste soil into GIS zeolite to remediate Cd-polluted soil - Lin Cai; Qian Zheng; Ziwei Wang; Zhouyang Tian; Dazhong Yang; Zhenhua Wei; Jingtao Hou (Journal of Hazardous Materials, 2025)

Multilevel surface enhancement of primary and secondary particles in cobalt-free high-nickel cathode material through Mo and W staged doping - Dandan Sun; Jiyuan Jian; Xin Zhang; Shuang Lin; Yixuan Qiao; Tao Wu; Xianhui Zhao; Rui Xiao; Ziwei Liu; Hua Huo; Pengjian Zuo; Yulin Ma; et al. (Chemical Engineering Journal, 2025)

Efficient carbon/phosphorus recovery from sludge anaerobic fermentation with recyclable MOF-based conductive materials activating sodium persulfate - Long Chen; Jianming Zhu; Ziwei Lin; Xiaohan Zhi; Zimu Qin; Hongtao Zhu (Resources, Conservation and Recycling, 2025)

Influence of disaccharide and mixed starter cultures on the fermentation process in earthen jar of factory-produced Sichuan paocai - Qiu Zhong; Hua Xiong; Shengshuai Li; Kaiyu Guo; Yue Shu; Xia Lin; Yage Xing; Ziwei Liang; Xingchen Liu; Lei Liu; Yu Rao (Food Research International, 2025)

Dabrafenib upregulates hypoglycosylated MUC1 and improves the therapeutic efficacy of Tn-MUC1 CAR-T cells - Ziwei Zhou; Yinghua Zhu; Jianli Zhao; Yiming Zhao; Wenkui Fu; Chao Zhou; Jinfang Hu; Yewen Zeng; Yiguang Lin; Hong An; Haibin Yin; Herui Yao; et al. (Science Bulletin, 2025)

Evaluating the interception mechanism and spatiotemporal response of PO43− to the transformation of Fe species in riparian zone - Ziwei Guo; Zhang Wen; Yiming Li; Li Lin; Hui Liu; Songhu Yuan (Journal of Hydrology, 2025)

High-efficiency Pb2+ removal by hydroxy-sodalite for point-of-use drinking water purification - Qian Zheng; Ziwei Wang; Zhouyang Tian; Lin Cai; Chengfeng Jiang; Lili Deng; Dazhong Yang; Zhenhua Wei (Journal of Hazardous Materials, 2025)

In situ growth of iron incorporated Ni3S2 nanosheet on nickel foam in mediating electron transfer to peroxymonosulfate for pollutant abatement - Yunjin Yao; Zhongming Tao; Hongwei Hu; Lijie Zhang; Ziwei Ma; Yaoyao Wang; Shiyang Lin; Shaobin Wang (Journal of Environmental Sciences, 2025)

Artificial Intelligence in the Training of Radiology Residents: a Multicenter Randomized Controlled Trial - Yanqiu Chen; Zhen Sun; Wenjie Lin; Ziwei Xv; Qichen Su (Journal of Cancer Education, 2025)

A novel solid-phase activization approach to activate kaolinite-rich soil for LTA zeolite synthesis - Qian Zheng; Ziwei Wang; Zhouyang Tian; Lin Cai; Chengfeng Jiang; Lili Deng; Dazhong Yang; Zhenhua Wei (Chemical Engineering Journal, 2025)

Distribution of long-chain polyunsaturated fatty acids and the effects of molasses on DHA production in Thraustochytrium sp. 26185 - Xi Xie; Ziwei Guo; Qinghua Mo; Junkai Luo; Li Lin; Huifan Liu; Gengsheng Xiao; Qin Wang (Algal Research, 2025)

A fully integrated, non-invasive, and multimodal wearable device for sweat stimulation, collection and multiple physiological signals analysis - Yuetao Zhang; Zijie Li; Xuejiao Fan; Yan Liu; Zhiqi Li; Ziwei Zheng; Zixin Lin; Wenshan Zhang; Qingci Mu; Guangquan Mo; Yong Xia; Lei Mou (Chemical Engineering Journal, 2025)

Decreases in frequency-dependent intrinsic activity of the default mode network are associated with depression and cognition in patients with postacute sequelae of SARS-CoV-2 infection - Yao Wang; Ziwei Yang; Xiumei Zheng; Xiao Liang; Lin Wu; Chengsi Wu; Jiankun Dai; Yuan Cao; Xianjun Zeng; Meng Li; Fuqing Zhou (Brain Structure and Function, 2025)

Selective anchoring of phosphate groups coupled with swift interlayer cation exchange for record-high capacity cobalt adsorption - Lingrong Zeng; Ziwei Yao; Dewei Li; Qingying Xiao; Ziwen Chang; Jingjing Fan; Shuigen Li; Mengling Li; Lin Ding; Penghui Shao; Xubiao Luo; Shenglian Luo (Resources, Conservation and Recycling, 2025)

Cold tolerance of postharvest fungal pathogens is regulated by the conserved high osmolarity glycerol (HOG) pathway - Wenjin Yan; Ziwei Su; Ganghan Zhou; Yuxuan Lin; Weiheng Ren; Jinglei Liao; Chuanxi Zhu; Congcong Wang; Dandan Ren; Yiwen Wang; Aruppillai Suthaparan; Ling Xu; et al. (Postharvest Biology and Technology, 2025)

Unconstrained measurement method and verification of thrust vector in small solid propulsion system - Wen Feng; Ziwei Ren; Gang Zhang; Yang Liu; Weihua Hui; Lin Sun (Advances in Space Research, 2025)

Fertilizer reduction and biochar amendment promote soil mineral-associated organic carbon, bacterial activity, and enzyme activity in a jasmine garden in southeast China - Fajun Yang; Weiqi Wang; Ziwei Wu; Jiahao Peng; Hongda Xu; Maoquan Ge; Shaoying Lin; Yu Zeng; Jordi Sardans; Chun Wang; Josep Peñuelas (Science of The Total Environment, 2024)

The hypoglycemic activity of buckwheat and the underlying mechanisms: A mechanistic review - Xiying Jin; Caian He; Ziwei Guo; Yixin Li; Yunlong Li; Jinming Gao; Min Wang; Lin Han (Food Bioscience, 2024)

Biochar addition under straw return reduces carbon dioxide and nitrous oxide emissions in acidic tea field soil - Ziwei Yan; Shuirong Tang; Zhilong He; Hongguang Cheng; Gratien Twagirayezu; Jinsong Zhao; Rongbiao Xiang; Ronggui Hu; Shan Lin (Journal of Environmental Management, 2024)

Occurrence, spatial distribution, and ecological risk of benzotriazole UV stabilizers (BUVs) in sediments from Bohai sea of China - Xing Liu; Xiaodan Pei; JiaoJiao Li; Yawen Wei; Hao Sun; Zilan Wu; Sha Wang; Jianmin Chen; Zhongsheng Lin; Ziwei Yao (Environmental Research, 2024)

Benzotriazole ultraviolet absorbents in surface waters and sediments of the Bohai Sea and North Yellow Sea: Spatial trends and influencing factors - Xing Liu; Zilan Wu; Xiaodan Pei; Tian Lin; Jiaojiao Li; Sha Wang; Zhigang Guo; Ziwei Yao (Science of The Total Environment, 2024)

Untargeted metabolomics analysis using UPLC-QTOF/MS and GC–MS to unravel changes in antioxidant activity and compounds of almonds before and after roasting - Xiao Shan; Lin Li; Yu Liu; Ziwei Wang; Binbin Wei; Zhongbo Zhang (Food Research International, 2024)

Effects of biodegradable microplastics and straw addition on soil greenhouse gas emissions - Ziwei Yan; Shan Lin; Ronggui Hu; Hongguang Cheng; Rongbiao Xiang; Han Xu; Jinsong Zhao (Environmental Pollution, 2024)

Zero-strain Co-doped Na2FeP2O7/carbon delivers superior rate capability and long-cycle stability for sodium ion batteries - Jianhong Gao; Ziwei Chen; Wei Cao; Jiale Chen; Ming Zhang; Feng Lin; Yongsheng Li; Waqar Ahmad; Min Ling; Chengdu Liang; Jun Chen (Chemical Engineering Journal, 2024)

Generalizability of machine learning models predicting 30-day unplanned readmission after primary total knee arthroplasty using a nationally representative database - Anirudh Buddhiraju; Michelle Riyo Shimizu; Henry Hojoon Seo; Tony Lin-Wei Chen; MohammadAmin RezazadehSaatlou; Ziwei Huang; Young-Min Kwon (Medical & Biological Engineering & Computing, 2024)

Associations of toxic metals and their mixture with hyperuricemia in Chinese rural older adults - Hongli Wang; Yan Zhang; Liang Sun; Xianwei Guo; Qiang Liu; Junzhe Li; Ziwei Tian; Xuqiu Cheng; Yuan Wang; Huaibiao Li; Bing Hu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2024)

Enhanced degradation of atrazine from soil with recyclable magnetic carbon-based bacterial pellets: Performance and mechanism - Jianhua Qu; Ziwei Li; Siqi Wang; Qiutong Lin; Zhiyu Zhang; Zhihuan Wu; Qi Hu; Zhao Jiang; Yue Tao; Ying Zhang (Chemical Engineering Journal, 2024)

Comparative Effects of Straw and Biochar on N2O Emissions from Acidic Soils - Feier Wang; Zhilong He; Xiuling Zhang; Javed Iqbal; Muhammad Shaaban; Ronggui Hu; Shan Lin; Ziwei Yan (Journal of Soil Science and Plant Nutrition, 2024)

Dissolved organic matter accelerates microbial degradation of 17 alpha-ethinylestradiol in the presence of iron mineral - Huan He; Min Shi; Xiaoxia Yang; Juhong Zhan; Yanting Lin; Ziwei Guo; Zhicheng Liao; Chaochao Lai; Xiaomin Ren; Bin Huang; Xuejun Pan (Journal of Environmental Sciences, 2024)

Genome-wide characterization of SmZHD gene family and the role of SmZHD12 in regulating anthocyanin biosynthesis in eggplant (Solanum melongena L.) - Qian Chen; XinQin Liu; Han Zhang; JinDi Wang; Lin Du; ZiWei Zhao; ShaoHang Li; YongJun He (Plant Cell Reports, 2024)

A new silicified microfossil assemblage from the Ediacaran Dengying Formation in South Shaanxi, China - Qiaokun Dai; Hong Hua; Jinzhou Luo; Xiao Min; Ziwei Liu; Song Zhang; Meng Gong; Lin Bai (Precambrian Research, 2024)

Assembly mechanisms and driving factors of aerobic denitrifying bacteria community with different seasons and rarity in the sediments of Baiyangdian Lake - Zhaoying Chen; Tinana Zhang; Ziwei Zhang; Lin Yue; Jiansheng Cui; Jiafeng Zhang; Shilei Zhou; Beibei Chai (Journal of Soils and Sediments, 2024)

Interface chemistry affected the digestion fate of ketogenic diet based on medium- and long-chain triglycerides - Xue Li; Yang Cheng; Zheng Xu; Xiujun Lin; Bolin Xu; Ziwei Wang; Pan Li; Binbin Nian (Food Research International, 2024)

The changes and correlation of IL-6 and oxidative stress levels in RAW264.7 macrophage cells induced by PAHs in PM2.5 - Jiaxin Liu; Hongqiu Li; Ziwei Guo; Xiang Xiao; Angelo Viscardi; Rongqi Xiang; Haobiao Liu; Xue Lin; Jing Han (Environmental Geochemistry and Health, 2024)

Spatiotemporal differentiation and attribution of land surface temperature in China in 2001–2020 - Hao Tian; Lin Liu; Zhengyong Zhang; Hongjin Chen; Xueying Zhang; Tongxia Wang; Ziwei Kang (Journal of Geographical Sciences, 2024)

Design strategies for renovation of public space in Beijing's traditional communities based on measured microclimate and thermal comfort - Ning Li; Zhao Guo; Wenying Geng; Lin Li; Ziwei Li (Sustainable Cities and Society, 2023)

Enhanced biological wastewater treatment supplemented with anaerobic fermentation liquid of primary sludge - Lin Li; Qiqi Liao; Caihong Liu; Tanglong Zhang; Chang Liu; Ziwei Chen; Rui Gao; Qiang He (Journal of Environmental Management, 2023)

Characterizing novel brominated flame retardants in the coastal atmosphere of the northern Bohai and Yellow Seas - Zilan Wu; Hao Sun; Xing Liu; Tian Lin; Tianfeng Guo; Wenwen Wang; Zhigang Guo; Ziwei Yao (Atmospheric Environment, 2023)

Investigating the presence of organophosphate esters in sediments from a typical fishing port agglomeration in Dalian, North China - Shilan Zhao; Xing Liu; Zilan Wu; Tian Lin; Hao Sun; Wenwen Wang; Zhigang Guo; Ziwei Yao (Environmental Pollution, 2023)

Single and Combined Effects of Short-Term Selenium Deficiency and T-2 Toxin-Induced Kidney Pathological Injury Through the MMPs/TIMPs System - Ziwei Guo; Mumba mulutula Chilufya; Huan Deng; Lichun Qiao; Jiaxin Liu; Xiang Xiao; Yan Zhao; Xue Lin; Haobiao Liu; Rongqi Xiang; Jing Han (Biological Trace Element Research, 2023)

Spatio-temporal pattern and attribution analysis of the mass elevation effect in the Tianshan Mountains in China - Mingyu Zhang; Zhengyong Zhang; Lin Liu; Xueying Zhang; Ziwei Kang; Hongjin Chen; Yu Gao; Tongxia Wang; Fengchen Yu (Journal of Geographical Sciences, 2023)

The intricate relationship between autoimmunity disease and neutrophils death patterns: a love-hate story - Ziwei Zhang; Lin Jin; Lianghu Liu; Mengqi Zhou; Xianzheng Zhang; Lingling Zhang (Apoptosis, 2023)

Comparative antioxidant activity and untargeted metabolomic analyses of cherry extracts of two Chinese cherry species based on UPLC-QTOF/MS and machine learning algorithms - Ziwei Wang; Lin Zhou; Wenqian Hao; Yu Liu; Xia Xiao; Xiao Shan; Chenning Zhang; Binbin Wei (Food Research International, 2023)

Comprehensive renovation and optimization design of balconies in old residential buildings in Beijing: A study - Ning Li; Xufeng Miao; Wenying Geng; Ziwei Li; Lin Li (Energy and Buildings, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

A series of bifunctional ReBaCo2O5+ perovskite catalysts towards intermediate-temperature oxygen reduction reaction and oxygen evolution reaction - Lin Li; Ziwei Dong; Tian Xia; Xiang Li; Qiang Li; Liping Sun; Hui Zhao; Lihua Huo (Chemical Engineering Journal, 2023)

Kinetics and mechanisms of bacteria disinfection by performic acid in wastewater: In comparison with peracetic acid and sodium hypochlorite - Ning Ding; Ziwei Li; Lin Jiang; Hong Liu; Yanping Zhang; Yingxue Sun (Science of The Total Environment, 2023)

Can urban polycentricity improve air quality? Evidence from Chinese cities - Will W. Qiang; Haowen Luo; Yuxuan Xiao; David W.H. Wong; Alex S. Shi; Ziwei Lin; Bo Huang; Harry F. Lee (Journal of Cleaner Production, 2023)

A simple AIE-active salicylideneaniline towards bimodal encryption-decryption with unique ESIPT-inhibited amorphous state - Xu-Min Cai; Weiren Zhong; Ziwei Deng; Yuting Lin; Zhenguo Tang; Xuedan Zhang; Jianyu Zhang; Wenjin Wang; Shenlin Huang; Zheng Zhao; Ben Zhong Tang (Chemical Engineering Journal, 2023)

Selenium nanoparticles: Properties, preparation methods, and therapeutic applications - Xiang Xiao; Huan Deng; Xue Lin; Ahmed Sameir Mohamed Ali; Angelo Viscardi; Ziwei Guo; Lichun Qiao; Yujie He; Jing Han (Chemico-Biological Interactions, 2023)

Spatiotemporal variations and impact factors of nutrients in the Sanya Bay, northern South China Sea - Xinxing Geng; Chuanliang Wu; Ziwei Yang; Junying Zhu; Kai Tang; Jiamin Lin; Yaxing Liu; Yufang Zhang; Mingxun An; Weibin Zhao; Yang Yu (Environmental Science and Pollution Research, 2023)

Insights into solid phase denitrification in wastewater tertiary treatment: the role of solid carbon source in carbon biodegradation and heterotrophic denitrification - Ziwei Chen; Qingyang Zuo; Caihong Liu; Lin Li; Katherine Y. Deliz Quiñones; Qiang He (Bioresource Technology, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Marine environmental monitoring with unmanned vehicle platforms: Present applications and future prospects - Shuyun Yuan; Ying Li; Fangwen Bao; Haoxiang Xu; Yuping Yang; Qiushi Yan; Shuqiao Zhong; Haoyang Yin; Jiajun Xu; Ziwei Huang; Jian Lin (Science of The Total Environment, 2023)

Polycyclic aromatic hydrocarbons in Fildes Peninsula, maritime Antarctica: Effects of human disturbance - Zilan Wu; Tian Lin; Hao Sun; Ruijing Li; Xing Liu; Zhigang Guo; Xindong Ma; Ziwei Yao (Environmental Pollution, 2023)

Crocetin confers neuroprotection and is anti-inflammatory in rats with induced glaucoma - Qiaoqiao Li; Peishi Feng; Susu Lin; Zijin Xu; Jiajing Zhao; Ziwei Chen; Zirui Luo; Yi Tao; Suhong Chen; Ping Wang (Molecular Biology Reports, 2023)

Does fiscal expenditure promote green technological innovation in China? Evidence from Chinese cities - Li Wei; Boqiang Lin; Ziwei Zheng; Wei Wu; Yicheng Zhou (Environmental Impact Assessment Review, 2023)

Non-invasive measurements of thermal discomfort for thermal preference prediction based on occupants' adaptive behavior recognition - Yanchen Liu; Hao Li; Peiping Zheng; Huijun Wu; Zhe Wang; Ziwei Li; Borong Lin (Building and Environment, 2023)

Detection of the role of intestinal flora and tryptophan metabolism involved in antidepressant-like actions of crocetin based on a multi-omics approach - Susu Lin; Qiaoqiao Li; Zijin Xu; Ziwei Chen; Yi Tao; Yingpeng Tong; Ting Wang; Suhong Chen; Ping Wang (Psychopharmacology, 2022)

Spatio-temporal correlation between human activity intensity and land surface temperature on the north slope of Tianshan Mountains - Hongjin Chen; Lin Liu; Zhengyong Zhang; Ya Liu; Hao Tian; Ziwei Kang; Tongxia Wang; Xueying Zhang (Journal of Geographical Sciences, 2022)

Ergosterol peroxide: an effect-directed detecting method from Anoectochilus elwesii and evaluation of anticancer activity - Yanduan Lin; Bingqin Wen; Ziwei Zhang; Jinyan Cai (Natural Product Research, 2022)

A Study on the Mechanism of Low-Expressed Cancer Stem Cell Marker Lgr5 in Inhibition of the Proliferation and Invasion of Colorectal Carcinoma - Houjun Jia; Lin Xiang; Ziwei Wang; Qipeng Zhou (Cell Biochemistry and Biophysics, 2015)

Aquatic predicted no-effect concentration for three polycyclic aromatic hydrocarbons and probabilistic ecological risk assessment in Liaodong Bay of the Bohai Sea, China - Ying Wang; Juying Wang; Jingli Mu; Zhen Wang; Ziwei Yao; Zhongsheng Lin (Environmental Science and Pollution Research, 2014)

Efficacy analysis of combining three comparative-omics profilings to screen candidate biological macromolecules - Ziwei Feng; Bei Lin; Yong Xu; Liancheng Zhu; Juanjuan Liu; Jian Gao (Molecular Biology Reports, 2013)

Manganese-Induced Effects on Testicular Trace Element Levels and Crucial Hormonal Parameters of Hyline Cocks - Xiao-fei Liu; Li-ming Zhang; Ziwei Zhang; Ning Liu; Shi-wen Xu; Hong-jin Lin (Biological Trace Element Research, 2013)